Benchmarking w procesie ciągłego doskonalenia - Kowalak, Robert (Benchmarking in continuous improvement, 2006)
The article presents the use of benchmarking in the process of continuous improvement. Managers analysing proposals prepared by workers from improvements units compare them with existing solutions and with solutions applied by other organizational units (e.g. branches, institutions, departments) and with solutions applied by other companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 209-215